The role of MMP-12 gene polymorphism − 82 A-to-G (rs2276109) in immunopathology of COPD in polish patients: a case control study - Iwona Gilowska; Edyta Majorczyk; Łukasz Kasper; Katarzyna Bogacz; Jan Szczegielniak; Marta Kasper; Jacek Kaczmarski; Aleksandra Skomudek; Marcin Czerwinski; Krzysztof Sładek (BMC, 2019)
Abstract Background Major symptoms of chronic obstructive pulmonary disease (COPD) are chronic bronchitis and emphysema leading from lung tissue destruction, that is an effect of an imbalance between metalloproteinases (MMPs) and their tissue inhibitors activity. As potential factor involved in this COPD pathogenesis, MMP-12 is considered. We investigated the role of genetic polymorphism and protein level of MMP-12 in the COPD development among Poles. Methods We analyzed − 82 A > G SNP in the promoter region of MMP-12 gene (rs2276109) among 335 smoked COPD patients and 309 healthy individuals, including 110 smokers. Additionally, 60 COPD patients and 61 controls (23 smokers) were tested for serum levels of MMP-12 using ELISA. All subjects were analyzed for lung function using spirometry (FEV1% and FEV1/FVC parameters). Results We observed that -82G allele and -82GG homozygous genotype frequencies of the SNP rs2276109 were significantly lower in COPD patients than in controls (12.5% vs 16.9%, respectively; χ2 = 4.742, p = 0.02 for allele and 0.5% vs 3.9%, respectively; χ2 = 9.0331, p = 0.01 for genotype). Moreover, −82G allele was more frequent in controls smokers than in non-smokers (22.3% vs 14.1%, χ2 = 6.7588, p = 0.01). Serum level of MMP-12 was significantly higher in COPD patients than in controls groups (6.8 ng/ml vs 3.3 ng/ml, respectively; F = 7.433, p < 0.0001), although independently of analyzed gene polymorphisms. Additionally, no correlation between parameters of lung function (FEV1% and FEV1/FVC) and protein level was found. Conclusions We found that -82G allele of SNP rs2276109 was associated with reduced risk of COPD, and COPD patients released more MMP-12 than healthy individuals, but independently on this SNP.